تداعيات التحولات السياسية في المنطقة العربية عمى العلاقات الخميجية القطرية 2011-2017[ - داسي, مريم (جامعة الوادي -University eloued, 2018)
جذور تاريخية منيا: الخلاف الحدودي الموروث عمى الإستعمار بين قطر والسعودية وبين قطر والإمارات, كذلك إنسحاب قطر من القمة الخميجية لسنة 2991واب ا رميا سة لسيا لإتفاقيات مع دولة إي ا رن, أيضاً تأسيسيا لقناة الجزيرة التي أعتبرت معادية حكام الخميج . شيدت الأزمة تطورات ميمة تمثمت في البداية بحملات إعلامية معادية لمسياسة القطرية والى غاية قطع كافة العلاقات السياسية والاقتصادية . للأزمة القطرية ثلاث إحتمالات إما بقاء الوضع الحالي أو رضوخ قطر لمتفاوض مع دول الحصار أو تصعيد الأزمة التي يمكن أن تتحول إلى نزاع مسمح بين الدول Historical roots, including: the border dispute inherited from colonialism between Qatar and Saudi Arabia And between Qatar and the Emirates, as well as Qatar's withdrawal from the Gulf Summit of the year 1992 and August s for sya For agreements with the state of Iran, also founding Al Jazeera, which was considered hostile Gulf rulers.  The crisis created important developments, initially represented by anti-political media campaigns country and until all political and economic relations are cut off.  The Qatari crisis has three possibilities: either the current situation will remain or Qatar will acquiesce to a negotiation with The blockading countries or the escalation of the crisis that could turn into a permissible conflict between countries
حكم راشد
Keywords: التحولات السياسية ، المنطقة العربية ، العلاقات الخليجية القطرية ]2011-2017; Political transformations, the Arab region, Gulf-Qatari relations ]2011-2017